Exploring the Medicinal Properties of Indigenous Plants Within an Enabling Program: Bridging the Gap Between School, Aboriginal and Torres Strait Islander Knowledge and Science. - Gough, Sharon; Sartori, Julie; Jones, Angela (Journal of University Teaching and Learning Practice, 2025)
In 2021, less than half of Australian universities considered Indigenous perspectives in curriculum development, with only 15% ensuring Indigenous content in all courses (Universities Australia, 2021). Literature acknowledges that a strengths-based approach to the inclusion of Aboriginal and Torres Strait Islander knowledge and perspectives, enhances representation and decolonises curriculum (Ah Chee et al, 2024; AIATSIS, 2022; Lukey et al., 2022; Fogarty et al., 2018). In 2020, Noongar elder Vivienne Hansen, and John Horsfall created Noongar Bush Medicine, detailing the medicinal use of Indigenous plants. Yeshi et al. (2022) noted that many Aboriginal and Torres Strait Islander communities use native plants for health purposes. However, there is limited data on the therapeutic efficacy of these plants. In 2024, the Science Unit Coordinator in ECU’s UniPrep enabling program (located on Whadjuk Noongar boodja and Wadandi boodja) designed a module examining the medicinal properties of indigenous plants, engaging students with Aboriginal and Torres Strait Islander knowledge as a core component of science. The experiment involved testing the medicinal use of: moorngan/Tea tree (Melaleuca radula), Eucalyptus (combination of species), uilarac/waang/ wolgol/wollgat/Sandalwood (Santalum spicatum), and honey using nutrient agar microplates inoculated with Escherichia coli and Staphylococcus epidermidis. This paper details the module’s design, experiment, and outcomes. Preliminary findings suggest that this initiative enhances student engagement and fosters appreciation for Aboriginal and Torres Strait Islander knowledge systems and STEM. This inclusive, hands-on learning module also addresses barriers faced by students from non-traditional backgrounds in accessing STEM, highlights the underrepresentation of Indigenous knowledge and science-focused curriculum in enabling education research.